Gestión de proyectos e indicadores de performance - Nieto Quispe, Luis Angel (2014)
The present document deals in detail with implementation and management aspects of the Project “Project Management and Performance Indicators”. The goal of this project is to provide the Software Consultant Altimea of a system that can display on a tangible and graphic fashion the performance of the projects it develops, in order to achieve greater profitability. The system consists of various software applications that interact with each other to store and visualize the most recent information from the tasks involved in Altimea’s projects, and deliver such information to project managers and clients. Projects are first processed through a website and its tasks are converted to Key Performance Indicators (KPIs), which can be accessed from smartphones with Android or IOS operative systems, or from tablets with IOS operative system.